Targeting amino acid in tumor therapy - Ge, Mingpai; Xu, Yuan; Cui, Lu; Huang, Enyuan; Liu, Zhaorui; Yin, Kai (Frontiers in Oncology, 2025)
Tumor cells undergo profound metabolic reprogramming to sustain their rapid growth and proliferation, with amino acids serving as essential nutrients critical for protein synthesis, energy metabolism, nucleotide production, and redox balance. The increased reliance of tumor cells on specific amino acids represents a promising therapeutic target. This review provides an in-depth analysis of the biological roles of amino acids in cancer, identifies vulnerabilities associated with amino acid dependency, and discusses strategies to leverage these weaknesses for enhanced cancer treatment. We explore the mechanisms governing amino acid uptake, utilization, and metabolism in tumor cells, as well as their interactions with the tumor microenvironment. Additionally, the review addresses the challenges and prospects of targeting amino acid metabolism in cancer therapy, including issues of resistance, the complexity of metabolic pathways, and the potential for personalized treatment approaches.